Petrogenesis of Rinjani Post-1257-Caldera-Forming-Eruption Lava Flows - Rachmat, Heryadi; Rosana, Mega Fatimah; Wirakusumah, Ade Djumarma; Jabbar, Gamma Abdul (Indonesian Journal on Geoscience, 2016)
DOI:10.17014/ijog.3.2.107-126After the catastrophic 1257 caldera-forming eruption, a new chapter of Old Rinjani volcanic activity beganwith the appearance of Rombongan and Barujari Volcanoes within the caldera. However, no published petrogeneticstudy focuses mainly on these products. The Rombongan eruption in 1944 and Barujari eruptions in pre-1944, 1966,1994, 2004, and 2009 produced basaltic andesite pyroclastic materials and lava flows. A total of thirty-one sampleswere analyzed, including six samples for each period of eruption except from 2004 (only one sample). The sampleswere used for petrography, whole-rock geochemistry, and trace and rare earth element analyses. The Rombonganand Barujari lavas are composed of calc-alkaline and high K calc-alkaline porphyritic basaltic andesite. The magmashows narrow variation of SiO2 content that implies small changes during its generation. The magma that formedRombongan and Barujari lavas is island-arc alkaline basalt. Generally, data show that the rocks are enriched in LargeIon Lithophile Elements (LILE: K, Rb, Ba, Sr, and Ba) and depleted in High Field Strength Elements (HFSE: Y, Ti,and Nb) which are typically a suite from a subduction zone. The pattern shows a medium enrichment in Light REEand relatively depleted in Heavy REE. The processes are dominantly controlled by fractional crystallization andmagma mixing. All of the Barujari and Rombongan lavas would have been produced by the same source of magmawith little variation in composition caused by host rock filter process. New flux of magma would likely have occurredfrom pre-1944 until 2009 period that indicates slightly decrease and increase of SiO2 content. The Rombongan andBarujari lava generations show an arc magma differentiation trend.